2004
DOI: 10.1089/154099904323016491
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Women's Responses to a Hospital Sleep Challenge: Aging and Menopause Effects on Sleep Architecture

Abstract: Aging-related sleep deficits in response to an experimental stressor occur in midlife women prior to menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…The objective and subjective sleep quality of premenopausal women was closer to that of postmenopausal women than that of young women. Studies exactly like ours are not available but our results are in line with the results of Lukacs et al 31 whose study was conducted under sleep challenge. 31 We could also reproduce the well-documented age-related sleep changes, such as the worsening of the overall sleep architecture and decline in slow wave sleep, between young women and the older groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The objective and subjective sleep quality of premenopausal women was closer to that of postmenopausal women than that of young women. Studies exactly like ours are not available but our results are in line with the results of Lukacs et al 31 whose study was conducted under sleep challenge. 31 We could also reproduce the well-documented age-related sleep changes, such as the worsening of the overall sleep architecture and decline in slow wave sleep, between young women and the older groups.…”
Section: Discussionsupporting
confidence: 93%
“…Studies exactly like ours are not available but our results are in line with the results of Lukacs et al 31 whose study was conducted under sleep challenge. 31 We could also reproduce the well-documented age-related sleep changes, such as the worsening of the overall sleep architecture and decline in slow wave sleep, between young women and the older groups. [32][33][34][35] The young women in our study were using OC.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, to what extent the unblinded nature of the protocol contributed to the reduction is symptoms is not known. Despite the presence of hot flashes during the study, sleep efficiency, although reduced as expected under the experimental conditions, was similar to that observed in healthy postmenopausal women without hot flashes undergoing a similar protocol [67]. …”
Section: Discussionsupporting
confidence: 69%
“…Kalleinen et al ( 33 ) studied older versus younger women and reported that sleep efficiency decreases with age and is not associated with decreasing estrogen levels. In contrast, other studies have shown greater difficulty in initiation and maintenance of sleep in postmenopausal woman than in premenopausal women, suggesting that sleep difficulties in middle-aged women are related to a decline in estrogen levels ( 34 , 35 ). Studies that examined the effect of estrogen supplementation on sleep disturbances in postmenopausal women have provided conflicting results.…”
Section: Discussionmentioning
confidence: 68%